2015
DOI: 10.3390/s150819181
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Driver Fatigue versus Alertness Using the Granger Causality Network

Abstract: Driving fatigue has been identified as one of the main factors affecting drivers’ safety. The aim of this study was to analyze drivers’ different mental states, such as alertness and drowsiness, and find out a neurometric indicator able to detect drivers’ fatigue level in terms of brain networks. Twelve young, healthy subjects were recruited to take part in a driver fatigue experiment under different simulated driving conditions. The Electroencephalogram (EEG) signals of the subjects were recorded during the w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(57 citation statements)
references
References 47 publications
3
50
0
4
Order By: Relevance
“…models robust to temporal variability of neural correlates, increased noise, interaction of neural processes. Some promising approaches include the use of novel features based on the connectivity across brain areas [6], [7], [15], [53]- [55] or the covariance across channels [56], deep learning [10], [57], as well as techniques for robust decoder training using limited samples such as transfer learning or semi-supervised approaches [9], [40], [58]- [61]. A recent review on current trends for EEG decoding in BMI applications can be found in reference [62].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…models robust to temporal variability of neural correlates, increased noise, interaction of neural processes. Some promising approaches include the use of novel features based on the connectivity across brain areas [6], [7], [15], [53]- [55] or the covariance across channels [56], deep learning [10], [57], as well as techniques for robust decoder training using limited samples such as transfer learning or semi-supervised approaches [9], [40], [58]- [61]. A recent review on current trends for EEG decoding in BMI applications can be found in reference [62].…”
Section: Discussionmentioning
confidence: 99%
“…Khushaba and colleagues extracted features using a Fuzzy mutual-information based wavelet packet transform on a combination of EEG, electrooculography (EOG) and electrocardiogram (ECG) signals recorded during simulated driving [4]. Alternatively, other researchers have explored whether different levels of fatigue could be discriminated based on interactions among different brain areas estimated using Granger causality [7], transfer entropy [6], or partial directed coherence [15]. Another approach has looked at the stability of the ICA-estimated neural sources [16].…”
Section: A Drowsiness Workload and Emergencymentioning
confidence: 99%
“…Kaminski and Blinowska noted that the spread of electrical activity becomes smeared by volume conduction, and they obtained clear and reproducible results in their study51. Similarly to many recent reports using EEG to assess brain functional connectivity183038455253545556, we also assessed functional connectivity patterns in scalp regions instead of in the source domain. We emphasize that both the experimental results and the analyses in the present study were restricted to brain-scalp regions.…”
Section: Discussionmentioning
confidence: 74%
“…Fatigue driving data. The DRI data were recorded through a fatigue driving experiment (Kong et al, 2015). This experiment included 12 subjects aged between 23 and 25.…”
Section: 14mentioning
confidence: 99%